2022
DOI: 10.20448/jeelr.v10i1.4313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Special Learning Technology on the Effectiveness of Pedagogical Ethics Formation in Future Teachers

Abstract: This study aims to identify the effectiveness of special training technology in the formation of the pedagogical ethics of future teachers, the problem of a regional university in the formation of pedagogical ethics among students and how the entire formation pedagogical ethics process takes place. The study included 102 students (aged 18–22) with pedagogical profiles who were all present. Expert assessment method, a scaling method for studying the level of formedness of the future teacher’s professional ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The findings also revealed that the independent efforts of students aimed at overcoming this contradiction are ineffective. The generally recognized shortcomings of university training are that students are overloaded with volumes of material being studied, insufficient development of independent work skills and a lack of self-realization skills (Nagima et al, 2023;Zhakupova, Kyakbaeva, Karimova, & Omarova, 2022).…”
Section: Research Contributionmentioning
confidence: 99%
“…The findings also revealed that the independent efforts of students aimed at overcoming this contradiction are ineffective. The generally recognized shortcomings of university training are that students are overloaded with volumes of material being studied, insufficient development of independent work skills and a lack of self-realization skills (Nagima et al, 2023;Zhakupova, Kyakbaeva, Karimova, & Omarova, 2022).…”
Section: Research Contributionmentioning
confidence: 99%
“…An intensive exchange of advanced experience in the functioning, continuity and integration of various educational systems in the 21st century is necessary to identify effective methods, forms and technologies for teaching mathematics, determine their optimal content and develop the personalities and cultures of full-fledged members of the world community (Darling-Hammond, Flook, Cook-Harvey, Barron, & Osher, 2020;Zhang, Tao, & Zheng, 2021). The updated content of education, the transition carried out in the Republic of Kazakhstan since 2016 and its implementation in educational and methodological complexes are now some of the most discussed topics in school education (Nagima et al, 2023;Ospankulov, Zhumabayeva, & Nurgaliyeva, 2023;Zhumash et al, 2021;Zhussupbayev et al, 2023). The main tasks in the process of teaching (in particular, mathematics) are to identify and develop productive, heuristic, creative, divergent and creative thinking, the formation of sustainable motivation for learning and self-improvement, teaching the skills of self-education and research work and the formation of an internal need for continuous self-improvement (Gunawan, Kartono, Wardono, & Kharisudin, 2022;Nufus & Duskri, 2018;Sukestiyarno, Mashitoh, & Wardono, 2021;Toheri, Winarso, & Haqq, 2019).…”
Section: Math Education In Kazakhstanmentioning
confidence: 99%
“…A capable competent who can autonomously and creatively solve professional problems and tasks, integrate knowledge and pedagogical skills in various contexts and be capable of creativity and professional selfimprovement is needed in Kazakhstan's modern, dynamically changing schools (Nagima et al, 2023;Ospankulov, Zhumabayeva, & Nurgaliyeva, 2023).…”
Section: Introductionmentioning
confidence: 99%